KARAKTERISTIK MINYAK ATSIRI DAUN PANDAN WANGI (Pandanus amaryllifolius Roxb.) HASIL PERLAKUAN LAMA CURING DAN LAMA EKSTRAKSI - Putra Adiyasa, I Wayan; Wartini, Ni Made; Sedana Yoga, I W Gede (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 2 No 2 (2014): September)
The aims of this study were to 1) determine the influence of curing time and extraction time, on the rendement and characteristics of essential oil of pandan wangi leaves 2) get curing time and extraction time procses to produce the highest yield and the best characteristics essential oil of pandan wangi leaves and 3) determine the type and composition of compounds in the essential oil of pandan wangi leaves. This research used randomized block design with factorial pattern. The first factor (curing time) consists of 3 level namely without curing, the 2 and 4 days process time, the second factor (extraction time) consists of 3 level using the 2, 3, and 4 hours process time. Each treatment grouped into 3 groups based on the time implementation. Objective variables measured were yield, and composition profiles of compounds in essential oil of pandan wangi leaves. Subjective variabel measured were the preference of aroma and aroma strength of the essential oil of pandan wangi leaves. The best treatment was determined with effectiveness index. The results showed that the curing time and extraction times had significant effect on the rendement and characteristics of essential oil of pandan wangi leaves. The extraction time of 3 hours and material conditions of curing 4 days was right treatment to produce essential oil of pandan wangi leaves with the highest rendement and the best characteristics, namely rendement 1.983 %, the aroma preference of 5.2 (between like and really like) and aroma strength 6.4. essential oil of pandan wangi contain 36 kinds of compounds with 16 compounds were not identified. Constituent compounds consists of classes alkane (46,66%), alkene (31,22%), aldehid (11,13%), and not identified (10,89%).
Keywords: 23,